2010
DOI: 10.5097/1300-0705.ucd.496-10.02
|View full text |Cite
|
Sign up to set email alerts
|

Peristomal skin complications: prevention, treatment and care

Abstract: Stoma i §lemi, çe §itli cerrahi disiplinler tarafmdan yaygin olarak gerçekle §tirllir. Stomadan kaynaklanan komplikasyonlar sik görülür. Komplikasyonlarm literatürde belirtilen oranlan büyük farkliliklar göstermektedir. Bu komplikasyonlann birey üzerindeki etkileri basit bir rahatsizliktan ya §ami tehdit etmeye kadar degi §ir. En yaygm görülen stoma komplikasyonlan arasinda peristomal deri problemleri bulunmaktadir. Cerrahi teknik ve deneyim, stomanm planli ya da acil açilmasi, hastanm yac/, obesite, diyabet g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
(53 reference statements)
0
3
0
2
Order By: Relevance
“…Often the child with colostomy believes the odor seepage that occurs during the colostomy bag change produces uncontrollable odor and gas release. These factors cause the colostomytized child to withdraw from society [3,5,15]. In this study, parents stated that they felt inadequate and ashamed because of their child's colostomy, did not want to show the colostomy to anyone, and felt only they should know about it.…”
Section: Social Isolationmentioning
confidence: 75%
See 2 more Smart Citations
“…Often the child with colostomy believes the odor seepage that occurs during the colostomy bag change produces uncontrollable odor and gas release. These factors cause the colostomytized child to withdraw from society [3,5,15]. In this study, parents stated that they felt inadequate and ashamed because of their child's colostomy, did not want to show the colostomy to anyone, and felt only they should know about it.…”
Section: Social Isolationmentioning
confidence: 75%
“…Coping Coldicutt (2013) and Abbasiasl et al (2021) reported that families' support for each other, social support networks, access to health care and quality of available health care affect parents' coping with this process [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. In this study, most of the parents stated that they consoled themselves with the thought that they would eventually overcome the problems associated with the colostomy, and they tried to get through this hard period by looking on the bright side.…”
Section: Cultiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ayrıca, seksüel fonksiyonlarda azalma ve cinsel yönden yetersizlik hissi ile cinsel yaşamlarında değişiklikler yaşayabilmektedirler. 5,7,13,14 Bu olgu sunumunda da stomalı olgu, torbadan sızıntı olmasından ve kokunun dışarı çıkmasından korktuğunu ifade etmiştir. Cinsel birleşme sırasında koku çıkması, eşinin birlikte olmak istememesinden korkma ve cinsel isteksizlik yaşama gibi endişelerinden bahsetmiştir.…”
Section: Discussionunclassified
“…13 Ameliyat öncesi dönemde başlayan bakım; stomalı bireyi bilgilendirme, stoma bölgesinin işaretlenmesi, sağlık ekibiyle birlikte bakımın sürekliliğini sağlama, stoma bakımını öğretme, bireylerin bağımsızlıklarını kazandırarak taburculuk sonrası stomaya uyumu sağlama, danışmanlık hizmeti verme, bireyin memnuniyetini sağlama ve oluşabilecek komplikasyonlardan korumayı içermektedir. 10,14 Hemşireler bu bütüncül bakımı yerine getirirken eğtim ve danışmanlık hizmetlerini de kullanarak birey ve ailesine destek olmalı, stomaya uyumu sağlamalı, ortaya çıkabilecek potansiyel veya gerçek sorunları belirleyebilmeli ve bireyi stoma ile yaşama hazırlamalıdır. 15 Stomalı bireyin sosyal yaşama hazırlandığı bu sürecin en iyi şekilde sürdürülmesi hemşireler ve sağlık ekibi üyelerinin desteğine bağlıdır.…”
unclassified